REATIVIDADE DE FÊMEAS NELORE COM DIFERENTES CONFORMAÇÕES DOS CHIFRES - BALTA, Anna Julia Velasques; MENDEZ, Victor Hugo Benassi; AMORIM, Lidianny dos Santos; COSTA, Everton Garcia Areco Ximenes; VILELA, Reíssa Alves; SANTOS, Tânia Mara Baptista (ANAIS DO ENIC, 2025)
-